Exploring the impact of freeform gameplay on players' experience: an experiment with maze games at varying levels of freedom of movement - Sotiris Kirginas; Dimitris Gouscos (Serious Games Society, 2017)
This paper describes an experiment which aims to examine whether different versions of the same game, which differ only in terms of freedom of movement that incurs varying degrees of freeform gameplay, elicit different kinds of player experiences. Seventy one children aged 9 and 11 from a Greek primary school participated in a research experiment with these different game versions. Post-tests were used to measure the children's opinion of these games and differences in the appeal of the versions were then attributed to the feature of freeform gameplay. The findings from the study demonstrated that the digital game that offers the greatest extent of freeform gameplay led to better gaming experience than the digital games with lower extent of freeform gameplay. The main contribution of the paper, therefore, is that the research conducted provides some evidence that freeform gameplay is an important factor of positive gaming experience, and as such it should be optimized. This can only be done by considering at the same time the cognitive capabilities and pre-existing skills and knowledge of users, in the sense that only a level of freeform gameplay harmonized with user capabilities can lead users to learn, which is the ultimate goal of serious games.